Towards the enhancement of asset management of critical equipment in SMEs: methodology and implementation proposal - Segura-Monge, Miguel Ángel (2024)
SMEs are small and medium-sized enterprises that arise from an idea of marketing a product or service. The growth of these companies entails an increase in the complexity of their organization. From the increase in internal structure to the relationship with some external actors, such as regulatory and fiscal entities, it poses challenges for which adequate preparation is not always available or the most efficient path to address them is not clear. An example of this can be seen with the management of company assets, which is often rudimentary and there is no quantified notion of the criticality of assets for the SME’s business. Through an Asset Management Model, an SME can chart a path towards efficient use of its assets, avoiding unnecessary expenses in repairs, as well as problems that can affect business continuity. This better use of assets results in greater value to the SME’s business model. This technical note proposes a methodology for the implementation of Asset Management based on the INTE/ISO 55001 standard. The objective is to adapt the different steps for the early implementation of Asset Management Models that are common in large consolidated companies to small and medium-sized enterprises. This methodology was validated in a real case study in a medium-sized company in Costa Rica. The results not only showed the rudimentary asset management in SMEs but also the viability of implementing an Asset Management Model in early stages of SMEs.